2018
DOI: 10.1186/s12955-018-0892-0
|View full text |Cite
|
Sign up to set email alerts
|

Patient-reported outcomes in patients with overactive bladder treated with mirabegron and tolterodine in a prospective, double-blind, randomized, two-period crossover, multicenter study (PREFER)

Abstract: BackgroundThe PREFER study was an assessment of medication tolerability, treatment preference and symptom improvement during treatment with mirabegron (M) and tolterodine (T) extended release (ER) in patients with overactive bladder (OAB). In this analysis of PREFER, patient-reported outcomes (PROs) were assessed during treatment.MethodsPREFER was a two-period, 8-week crossover, double-blind, phase IV study (NCT02138747) of treatment-naïve adults with OAB ≥3 months randomized to 1 of 4 treatment sequences (M/T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…A two-period crossover study (PREFER), during which patients were randomized to receive mirabegron or tolterodine in one of four sequences (mirabegron–tolterodine, tolterodine–mirabegron, mirabegron–mirabegron, or tolterodine–tolterodine), reported similar mean OAB-q SF improvements for each of the treatments. However, patients were more likely to achieve clinically relevant improvements in HRQoL during mirabegron treatment [21]. Moreover, the PREFER study demonstrated improved tolerability for mirabegron compared with tolterodine.…”
Section: Discussionmentioning
confidence: 99%
“…A two-period crossover study (PREFER), during which patients were randomized to receive mirabegron or tolterodine in one of four sequences (mirabegron–tolterodine, tolterodine–mirabegron, mirabegron–mirabegron, or tolterodine–tolterodine), reported similar mean OAB-q SF improvements for each of the treatments. However, patients were more likely to achieve clinically relevant improvements in HRQoL during mirabegron treatment [21]. Moreover, the PREFER study demonstrated improved tolerability for mirabegron compared with tolterodine.…”
Section: Discussionmentioning
confidence: 99%
“…16 Herschorn et al conducted a double blind randomized multicenter trial for the efficacy of Mirabegron in the patients of OAB (PREFER) and found Mirabegron to be effective in relieving the symptoms of urgency in the patients with OAB. 17 We similarly found mirabegron to be effective in the treatment of nocturia and urge incontinence.…”
Section: Discussionmentioning
confidence: 85%
“…In this study, we demonstrated that Amibegron treatment signi cantly improved muscle regeneration and hindlimb function after VML. Mirabegron, a β3 adrenergic receptor agonist, with a similar structure to Amibegron, has been approved by the FDA for treating over-reactive bladders [43,44]. Though it may mildly increase heart rate and blood pressure in patients, Mirabegron could be considered as a potential novel treatment for VML in the future.…”
Section: Discussionmentioning
confidence: 99%